PENGARUH PENGGUNAAN AIR SEBAGAI FILTER TERHADAP DAYA PENYERAPAN EMISI NOX PADA GAS BUANG MOTOR BAKAR BENSIN - Rusmariadi, I Komang (Bumi Lestari, 2010)
The purpose of this research is to answer of the research problem which observed the influence of the water level within the filter to the rate of the absorption to the NOX emission. The achievement of the above goal will provide the answer about the effectiveness of water as a filter for NOX to be used for any practical purpose. The results ofb The research expected to be useful as the preliminary step in providing a simply designed filter in overcoming the pollution of the environment. In this research, the exhaust gas from gasoline engine was drawn into a reservoir filled with water before being released to the atmosphere. NOX emission was measured using Automotive Emission Analyzer before and after the use of water filter. It was hypothesized that the length of the path through which the exhaust gas passing the water will affect the rate of the absorption of the NOX. Hence, the measurement of the influence of the water level of the filter to its rate of the NOX absorption was done. The data obtained from the measurement was statistically analyzed using least-square linear and nonlinear regression methods. The analysis showed that the higher the water level on the filter, the higher its rate of absorption to the NOX emission. The regression analysis showed that the second order polynomial equation was the best in representing the relationship of the research variables compared to the linear and exponential regressions.